Cost Recovery Rate Unit Hemodialisa Rumah Sakit ABC Tahun 2006-2008 - Supriadi, Supriadi (UI Scholars Hub, 2013)
This research is motivated by the thought that Hemodialysis Unit at ABC hospital which opened in 2005 , is a unit that produces , but in the determination of rates of hemodialysis services have not been done in detail , which includes only the cost component of operating costs of direct material regardless of personnel costs , telephone and general logistics costs . The issue is whether income rates that have not been calculated in detail to cover the costs incurred by the unit or how hemodilisia Cost Recovery Rate ( CRR ) of the Hemodialysis Unit.This study is a qualitative study using secondary data from monthly reports of several ABC RS unit to calculate total revenue and total cost Haemodialysis Unit. The data used is the data of 2006,2007and2008.The results showed CRR Haemodialysis Unit 2006 = 41.69 % , 2007 = 71.36 % and 2008 = 83.11 %.Based on the results obtained during the 3 years that CRR is still below 100 % , it indicates that the income earned Haemodialysis Unit for 3 years has not been able to cover the costs incurred for the operation of the unit.